Outcome of acute heroin overdose requiring intensive care unit admission - Grigorakos, MD, PhD, Leonidas; Sakagianni, MD, Katerina; Tsigou, MD, Evdoxia; Apostolakos, MD, George; Nikolopoulos, MD, Giannis; Veldekis, MD, Dimitris (Journal of Opioid Management, 2018)
Background: Heroin use carries a large burden of morbidity and mortality. Heroin overdose and in particular events that need intensive care unit (ICU) admission have not been widely examined. The aim of this study was to describe the causes of ICU admission and the outcome of patients with a heroin overdose. Methods: A retrospective chart review of all patients with a heroin overdose admitted to the ICU between 1987 and 2006 was conducted. Results: Forty-two records were available for review. The average age of the patients was 28 years. In the field, 19 persons were found in coma Glasgow Coma Scale (GCS < 8) and respiratory depression and were treated with naloxone. The reasons for ICU admission included hypoxemia in 37 (88 percent), 28 of whom had acute lung injury (ALI) and nine aspiration pneumonia, shock in three (7.2 percent) and persistent mental compromise in two patients (4.8 percent). Intubation and mechanical ventilation (MV) were instituted in 37 patients. In 19 of the 37 patients, weaning and extubation became possible within the first 24 hours. Sixteen patients suffered complications and received MV for 5 ± 2 days, with a mean length of ICU stay of 8 ± 1 days, while two patients succumbed because of anoxemic encephalopathy and brain death. The complications observed were acute respiratory distress syndrome in eight patients, severe sepsis in four, catheter-related bacteremia in one, iatrogenic pneumothorax in one, and rhabdomyolysis in two, while four among them died due to severe sepsis. Conclusions: In our study, ALI and aspiration pneumonia were the most frequently observed respiratory complications after acute heroin overdose requiring intubation and ICU admission. Mortality rate was 14.2 percent and was attributed to septic complications and irreversible brain damage.